Ganoderma neo-japonicum Imazeki revisited: Domestication study and antioxidant properties of its basidiocarps and mycelia - Tan, Wee Cheat; Kuppusamy, Umah Rani; Phan, Chia Wei; Tan, Yee Shin; Raman, Jegadeesh; Anuar, Azliza Mad; Sabaratnam, Vikineswary (Nature Research, 2015)
Mushroom cultivation benefits humankind as it deliberately encourages wild mushrooms to be commercially propagated while recycling agricultural wastes. Ganoderma neo-japonicum is a rare polypore mushroom found growing on decaying Schizostachyum brachycladium (a tropical bamboo) clumps in Malaysia. The Malaysian indigenous tribes including the Temuans and Temiars use the basidiocarps of G. neo-japonicum to treat various ailments including diabetes. In this study, the domestication of G. neo-japonicum in artificial logs of different agricultural residues was investigated. Sawdust promoted the mycelia spawn colonisation in the shortest period of 38±0.5 days. However, only sawdust and bamboo dust supported the primodia formation. Complex medium supported mycelium growth in submerged cultures and 27.11±0.43g/L of mycelia was obtained after 2 weeks of cultivation at 28°C and 200rpm. Antioxidant potential in mushroom may be influenced by different cultivation and extraction methods. The different extracts from the wild and cultivated basidiocarps as well as mycelia were then tested for their antioxidant properties. Aqueous and ethanol extracts of mycelia and basidiocarps tested had varying levels of antioxidant activities. To conclude, domestication of wild G. neo-japonicum using agroresidues may ensure a continuous supply of G. neo-japonicum for its medicinal use while ensuring the conservation of this rare species.